Responsibility Center Budgeting as a Mechanism to Deal with Academic Moral Hazard - Myers, Gordon M. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2019)
Universities face inherent informational asymmetries. These make university budgeting prone to various challenges including moral hazard. The last forty years has seen some large research- intensive universities move from centralized incremental budgeting to decentralized Responsibility Center Budgeting (RCB). It is assumed that a faculty chooses a level of costly effort in generating revenue for the university. The level of faculty effort is not observable by the central administration. When there is no revenue uncertainty or when the faculty is not risk averse, pure RCB is best from the perspective of the administration. The intuition is that pure RCB fully aligns financial responsibility with academic authority, that is, it makes the faculty the residual claimant. Once the faculty is risk averse, partial RCB is optimal. Partial RCB provides a balance between providing the right incentives to the faculty and the university reducing the revenue risk faced by the faculty.